Wykorzystanie decyzyjnych rachunków kosztów w zarządzaniu ryzykiem zakładów ubezpieczeń - Chmielowiec-Lewczuk, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Risk management is very important for insurance companies' activities (technical, investment and reinsurance). In these financial institutions there are four kinds of risk: underwriting risk, credit risk, market risk and operational risk. For underwriting risk it should be used cost accounting which generates information about insurance product' costs calculation. For credit risk it could be applied investment cost calculation system and for market risk cost accounting of reinsurance activity. The last kind of risk - operational could be minimized in result of using information about other costs which are connected with each business activity. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 36-43